Tirzepatide versus semaglutide for weight loss in patients with type 2 diabetes mellitus: A value for money analysis. Issue 4 (27th December 2022) - Azuri, Joseph; Hammerman, Ariel; Aboalhasan, Enis; Sluckis, Ben; Arbel, Ronen
Abstract: Aims: Higher doses of the glucagon‐like peptide‐1 agonist semaglutide and, more recently, tirzepatide, a dual glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 agonist showed a significant reduction in body weight in patients with type 2 diabetes mellitus. However, their comparative value for money for this indication is unclear. Therefore, we aimed to establish which provides better value for money. Materials and Methods: We calculated the cost needed to treat to achieve a 1% reduction in body weight using high‐dose tirzepatide (15 mg) versus semaglutide (2.4 mg). The body weight reductions were extracted from published results of SURMOUNT‐1 and STEP 1 trials, respectively. In addition, we performed a scenario analysis to mitigate the primary differences between the two study populations. Drug costs were based on US GoodRx prices as of October 2022. Results: Using tirzepatide resulted in a weight loss of 17.8% (95% CI: 16.3%‐19.3%) compared with 12.4% (95% CI: 11.5%‐13.4%) for semaglutide. The total cost of 72 weeks of tirzepatide was estimated at 17 527 compared with 22 878 for 68 weeks of semaglutide. Accordingly, the cost needed to treat per 1% of body weight reduction with tirzepatide is estimated at 985 (95% CI: 908‐1075) compared with 1845 (95% CI: 1707‐1989) with semaglutide. Scenario analysis confirmed these findings. Conclusions: Tirzepatide provides better value for money than semaglutide for weight reduction.